Management of Pyrexia Associated with the Combination of Dabrafenib and Trametinib: Canadian Consensus Statements - Alia Thawer; Wilson H. Miller; Nancy Gregorio; Joël Claveau; Sudha Rajagopal; Kerry J. Savage; Xinni Song; Teresa M. Petrella; on behalf of the Canadian Working Group (Current Oncology, 2021)
The combination of dabrafenib and trametinib is a well-established treatment for BRAF-mutated melanoma. However, the effectiveness of this approach may be hindered by the development of treatment-related pyrexia syndrome, which occurs in at least 50% of treated patients. Without appropriate intervention, pyrexia syndrome has the potential to worsen and can result in hypotension secondary to dehydration and associated organ-related complications. Furthermore, premature treatment discontinuation may result in a reduction in progression-free and overall survival. Despite existing guidance, there is still a wide variety of therapeutic approaches suggested in the literature for both the definition and management of dabrafenib and trametinib-related pyrexia. This is reflected in the practice variation of its prevention and treatment within and between Canadian cancer centres. A Canadian working group was formed and consensus statements were constructed based on evidence and finalised through a two-round modified Delphi approach. The statements led to the development of a pyrexia treatment algorithm that can easily be applied in routine practice. The Canadian working group consensus statements serve to provide practical guidance for the management of dabrafenib and trametinib-related pyrexia, hopefully leading to reduced discontinuation rates, and ultimately improve patients’ quality of life and cancer-related outcomes.